ANALISI BUDAYA ORGANISASI DALAM MENINGKATKAN KEPUASAN KERJA KARYAWAN PADA HOTEL HAPPY INN KENDARI - Nurhalija, Wa Ode St Nurhalija; jopang, jopang; Liwaul, Liwaul (Universitas Halu Oleo, 2017)
The formulation of the problem in this study was to find out how Organizational Culture in Improving Employee Satisfaction at Happy Inn Hotel Kendari, The data analysis technique used in this study was descriptive qualitative and the data collection techniques used in this study were observation, interviews and documentationFrom the results of the study show that organizational culture forms employees who are able to adapt to the environment and unites members of the organization to improve results every day the employee is trained and guided effectively and job satisfaction can also be interpreted as a match between the expectations of an employee with the benefits he gets from the work becomes an organizational culture and job satisfaction are interconnected.